Comment on ‘Surface Plasmons and Nonlocality: A Simple Model’ Reply - Luo, Yu (2016)
In the Comment [1], Schaich calculated the mode dispersion of surface plasmons supported by a planar metal-dielectric-metal (MIM) structure, and concluded that our model [2] fails to mimic the effect of nonlocality at high frequencies. Here, we shall clarify the difference between our calculations and that in Schaich’s Comment, and highlight the validity of our model for a general class of plasmonic structures.